Late-Onset Nephropathic Cystinosis: Clinical Presentation, Outcome, and Genotyping - Servais, Aude (American Society of Nephrology, 2008)
Background and objectives: Cystinosis is an autosomal recessive disease characterized by the intralysosomal accumulation of cystine, as a result of a defect in cystine transport across the lysosomal membrane. Three clinical forms have been described on the basis of severity of symptoms and age of onset: infantile cystinosis, characterized by renal proximal tubulopathy and progression to end-stage renal disease before 12 yr of age; juvenile form, with a markedly slower rate of progression; and adult form, with only ocular abnormalities. Design, setting, participants, & measurements: Fourteen patients in nine unrelated families with noninfantile cystinosis were studied. Information about clinical outcome, biochemical data, renal histopathologic data, and genotyping was collected. Results: Eight patients had Fanconi syndrome. Proteinuria was present in all patients. Serum creatinine at last follow-up, without specific treatment, ranged between 69 and 450 μmol/L, at an age of 12 to 56 yr. Four patients reached end-stage renal disease by 12 to 28 yr. Renal biopsies, available in four cases, disclosed focal segmental glomerulosclerosis in three and crystals in three. Genetic screening showed that patients were compound heterozygous for mutations in the CTNS gene in four families and homozygous in two families. Patients had at least one “mild” mutation. A single heterozygous mutation was identified in one family and none in two families (only 72% mutations found). Conclusion: Renal involvement is heterogeneous in patients with noninfantile cystinosis even within families, and renal disease should be assessed even in families of patients with seemingly isolated ocular forms.